2012
DOI: 10.1597/10-237
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological, Behavioral, and Academic Sequelae of Cleft: Early Developmental, School Age, and Adolescent/Young Adult Outcomes

Abstract: This article reviews behavioral, neuropsychological, and academic outcomes of individuals with cleft across three age levels: 1) infancy/early development, 2) school age, and 3) adolescence/young adulthood. The review points out that attachment, neurocognitive functioning, academic performance/learning, and adjustment outcomes are the result of a complex interaction between biological and environmental factors and vary with developmental level, sex, and craniofacial anomaly diagnosis. The degree to which assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 76 publications
(131 reference statements)
2
94
0
10
Order By: Relevance
“…The classmate sample is more than double that of affected children because we compared affected children to all of their matched controls on all grades with available ITP data (before and after switching school districts). This approach preserved the classmate sample composition when comparing academic achievement over multiple grades (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) or school levels instead of including classmate data only for overlapping grades with the affected child (which would include different classmates at different grades for children who switched school districts). Also, this comparison reduces potential biases from selective switching on the basis of the child' s academic performance and characteristics of the new school district.…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The classmate sample is more than double that of affected children because we compared affected children to all of their matched controls on all grades with available ITP data (before and after switching school districts). This approach preserved the classmate sample composition when comparing academic achievement over multiple grades (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) or school levels instead of including classmate data only for overlapping grades with the affected child (which would include different classmates at different grades for children who switched school districts). Also, this comparison reduces potential biases from selective switching on the basis of the child' s academic performance and characteristics of the new school district.…”
Section: Study Samplementioning
confidence: 99%
“…[3][4][5] Several studies have shown that children with isolated clefts have an increased incidence of learning problems and academic underachievement. 6 This work focused primarily on reading and, although there are exceptions, 7 most studies reported that affected children score lower than expected compared with test norms and unaffected controls. [8][9][10][11][12] However, population-based investigations are rare, and most studies have included small, clinicbased patient samples.…”
mentioning
confidence: 99%
“…Among the interfering conditions concerning reading and writing, the cognitive-linguistic disabilities are present, resulting from alterations in the language components. Longitudinal researches in literature show that children with cleft lip and palate present increased risk for language deficits, since they exhibit significantly lower scores in receptive and expressive language, when compared to children without cleft lip and palate [4][5][6] . The children with cleft lip and palate may present speech 7 , orthodontic 8 and emotional 3 , disabilities, and therefore these conditions are considered as risk factors for low academic performance 9 .…”
Section: Introductionmentioning
confidence: 99%
“…These conditions arise from developmental failures of neural crest cells during gestation, resulting in deformities of the oral and/or facial structure. Developmentally, these conditions are characterized by an increased incidence of developmental problems including language and intellectual impairment, learning disabilities, attentional deficits and impaired social function [1,2,3,4,5,6,7]; for a review, see Richman et al [8]. To date, the underlying etiology of these deficits remains unclear.…”
Section: Introductionmentioning
confidence: 99%